Gendered impacts of training and factors influencing Good Agricultural Machinery Manufacturing Practices Adoption in Bangladesh - Aravindakshan, Sreejith; Parupalli, V.L. Bharathi; Arafat, Moksedul; Saiful Islam; Azahar Ali Miah; Calvert, Owen D.; Krupnik, Timothy J. (TAFSSA, 2024)
This study examined the gendered impact of training and the factors influencing the adoption of Good Agricultural Machinery Manufacturing Practices (GAMMP) in Bangladesh, with a focus on understanding adoption levels, barriers, and enabling factors among trained and untrained men and women. The research aimed to provide evidence-based insights to enhance adoption rates and address gender disparities in agricultural machinery manufacturing in the Agricultural-Based Light Engineering (ABLE) sector.